Optimasi Pendistribusian Beras Bansos Menggunakan Metode Improved Zero Point di Perum Bulog Kantor Cabang Padang Sidempuan - BATUBARA, RISKA AMALIA; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2024)
Social Assistance Rice is a type of Government Rice Reserve rice which is provided free of charge to Beneficiary Families. Perum Bulog Padang Sidempuan Branch Office is tasked with providing and distributing Social Assistance Rice to destination Regency orCity. In distributing social assistance rice to destination areas, it costsquite a lot, namely Rp. 178.843.350. This includes transportation problems that can be solved using transportation methods. The application of the transportation method means obtaining an allocation of distribution of goods that can minimize total transportation costs. One method of transportation is the Improved Zero Point method which is a direct method without looking for an initial solution first and this method is good and efficient to use to get the optimal solution. From calculations using the Improved Zero Point method, the costs incurred are Rp. 177.971.180. So implementing this method can save distribution costs of Rp. 872.170.